2021
DOI: 10.1007/s15010-021-01622-9
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: attitudes towards Covid-19 vaccination among hospital employees in a tertiary care university hospital in Germany in December 2020

Abstract: Coronavirus disease 2019 (Covid-19) vaccination is essential to fight the pandemic. Health care workers (HCWs) are prioritized to get vaccinated, yet uptake of recommended vaccinations is known to be low in this group. In a tertiary care university hospital with a high number of Covid-19 patients in intensive care, 59.5% of surveyed staff (N = 2454) were willing to get vaccinated, 21.4% were unsure and 18.7% refused. Vaccine hesitancy was higher in female, younger and healthy employees without contact to Covid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
(14 reference statements)
4
15
0
1
Order By: Relevance
“…According to a meta-analysis, nursing staff were the most frequently affected group of workers at 48% [23]. However, surveys showed that the vaccination willingness among nursing staff in particular was low [11,13,15,19]. At the beginning of the vaccination campaign, vaccination willingness rates stood between 50% and 70% depending on the professional group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a meta-analysis, nursing staff were the most frequently affected group of workers at 48% [23]. However, surveys showed that the vaccination willingness among nursing staff in particular was low [11,13,15,19]. At the beginning of the vaccination campaign, vaccination willingness rates stood between 50% and 70% depending on the professional group.…”
Section: Discussionmentioning
confidence: 99%
“…In late 2020 and early 2021, HCWs from a range of fields in Germany were asked about their vaccination willingness. Initially, vaccination willingness was rather low (between 57% and 64%), but it increased to 76% as the vaccination campaign progressed [11][12][13][14]. Acceptance was markedly higher among physicians than among nursing staff (81% vs. 71%).…”
Section: Introductionmentioning
confidence: 98%
“…The recent cross-sectional study conducted in 2021 in Poland and Germany [30,31] revealed that respectively 51.9%/59.5% of the surveyed respondents, including HWs were willing to become vaccinated, 17.4%/21.4% were hesitant but might consider it in future, and 24.4%18.7% were against any inoculation. This indicates the need for the constant reinforcement of new strategies to reduce vaccine hesitancy, even in staff in the healthcare sector.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning to non-HCWs, the level of positive attitude towards COVID-19 vaccine among non-HCWs was ranged from 21.4% [53] to 91.99% [54]. Factors associated with the attitude towards COVID-19 vaccine among non-HCWs were age [70,71,77,78,88,91], gender [53,70,73,77,78,80,87,90], educational level [70,90], occupation [70,87], marital status [53,90], residency [74,90], income [77,78], ethnicity [78], risk for severe course of COVID-19 [70], direct contact with COVID-19 at work [70], being a health profession [71,80], being vaccinated against seasonal u [70,71,90], perceived bene ts [71], cues to actions [71], having previous history vaccination [73], fear of passing on the disease to relatives [54], and the year of medical study [54], studying health-related courses [74], COVID-19 concern [77], adherence level to social distancing guidelines [78], history of chronic disease [87], being pregnancy …”
Section: Search Resultsmentioning
confidence: 98%